Implications of Therapeutic Communication for Avoiding Lawsuits in Health Services - Luh Putu Eka, Sriwijayanti; I. Wayan Gede Artawan Eka, Putra; R.A. Tuty, Kuswardhani; I. Nyoman, Bagiastra (INTI International University, 2024)
Health services in Indonesia have a very important role in improving the welfare of the Republic of Indonesia. To prevent misunderstandings between patients and paramedics in health services, good communication is needed. Communication in health services can be called therapeutic communication. Previous research mostly only highlights the importance of using informed consent as valid proof of a therapeutic agreement, therefore in this research the important point is that in implementing informed consent, adequate, detailed, and easy to understand information must be given to the patient, this can be done by providing information using therapeutic communication. This article uses a literature study of legal research methods with a normative approach and a conceptual approach. Sources of research material used in this literature review include journal articles, legal regulations, and books. Therapeutic communication should be carried out in the entire series of patient care, especially in conveying informed consent, where the patient must receive a detailed explanation regarding the diagnosis, therapy plan, risks if treatment is carried out or not carried out, and the treatment prognosis, so that the patient can determine properly what treatment is needed. will be chosen consciously. When the treatment carried out is determined by the patient and carried out based on mutual agreement, this will reduce the possibility of disputes between the doctor and the patient. Therapeutic communication cannot completely prevent lawsuits and medical disputes, but by carrying out effective therapeutic communication, patients and paramedics can have equal views regarding the patient's condition, treatment plans, and the risks that may occur if medical action is or is not carried out.